POLA KONSUMSI DAN TINGKAT KETAHANAN PANGAN RUMAH TANGGA MISKIN DI KECAMATAN GADINGREJO KABUPATEN PRINGSEWU - Agustina, Yolanda; Prasmatiwi, Fembriarti Erry; Adawiyah, Rabiatul (Lampung University, 2020)
This research aimed to analyze the food consumption pattern, the level of food security, and factors that affected the level of food security of poor households. The location was chosen purposively at Gadingrejo Subdistrict, Pringsewu Regency in which respondents were 61 poor households. The data of this research were primary data and secondary data collected in April – Mei 2018 and analyzed using statistic descriptive analysis, cross classification between the share of food expenditure and availability in addition to food sufficiency level, and ordinal logistic regression analysis. The results of this research showed that there were 14 types of food consumed by households per day, the household PPH score of Demapan Program members was 69.78 and nonmembers was 65.62. As many as 46.67 percent member households of Demapan Program and 35.48 percent nonmember households of the Program were classified as food secured. The factors affected the level of food security were household income, the number of household members, and price of the rice. There was no difference in the level of food security between member and nonmember households of Demapan Program.Key words: consumption pattern, demapan program, food security